Generating economic growth: An analytical survey - Maria Thompson (The Open Economics Journal, 2008)
The theoretical richness and variety of the new growth literature can make it difficult to capture the essence of growth models. With this paper, we wish to provide one possible integrating view of the nature of the growth generating processes. Revisiting the models that constitute the core of growth theory, we expose analytically the main mechanisms through which long-run growth can be delivered. Models that contemplate physical capital accumulation generate long-run growth through the attainment of a nondeclining marginal productivity of capital. One mechanism for achieving this entails the introduction of technological progress; another mechanism involves the inclusion of human capital accumulation; and a third method relies on the elimination from the production function of the diminishing returns to capital feature. The foundational models that classically represent each of these mechanisms are reviewed in an analytical and integrating perspective. Some growth models do not contemplate physical capital and hence obtain long-run growth without generating a nondeclining marginal productivity of capital. We look into two reference models of this nature.
Keywords: O3; O4; 330; non-diminishing returns to capital; economic growth; research & development; human capital accumulation; inada conditions.